2010
DOI: 10.1074/jbc.m109.033597
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase Propeptide Inhibits FGF-2-induced Signaling and Proliferation of Osteoblasts

Abstract: Pro-lysyl oxidase is secreted as a 50-kDa proenzyme and is then cleaved to a 30-kDa mature enzyme (lysyl oxidase (LOX)) and an 18-kDa propeptide (lysyl oxidase propeptide (LOX-PP)). The presence of LOX-PP in the cell layers of phenotypically normal osteoblast cultures led us to investigate the effects of LOX-PP on osteoblast differentiation. Data indicate that LOX-PP inhibits terminal mineralization in primary calvaria osteoblast cultures when added at early stages of differentiation, with no effects seen when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 77 publications
7
49
0
Order By: Relevance
“…Also, studies have found that LOX can bind to, and inhibit the signaling of, growth factors, including TGF-b1 and Fibroblast Growth Factor (FGF-2), albeit in non-cardiac cells. 46,47 The detrimental effects of TGF inhibition on the stressed heart were demonstrated using a dominant negative TGF-receptor mouse model. 48 In response to pressure overload, mice with reduced TGF Figure 8 Lysyl oxidase (LOX) inhibition (B) attenuated volume overload (VO)-induced increases in collagen I and III, but did not alter elastin expression.…”
Section: 32-36mentioning
confidence: 99%
“…Also, studies have found that LOX can bind to, and inhibit the signaling of, growth factors, including TGF-b1 and Fibroblast Growth Factor (FGF-2), albeit in non-cardiac cells. 46,47 The detrimental effects of TGF inhibition on the stressed heart were demonstrated using a dominant negative TGF-receptor mouse model. 48 In response to pressure overload, mice with reduced TGF Figure 8 Lysyl oxidase (LOX) inhibition (B) attenuated volume overload (VO)-induced increases in collagen I and III, but did not alter elastin expression.…”
Section: 32-36mentioning
confidence: 99%
“…Consistent with these findings, Bouez et al showed that LOX protein expression was absent from human basal and squamous cell carcinomas and that a reduction in LOX mRNA levels but not enzyme activity caused a more invasive phenotype in a HaCaT skin equivalent model (3). In H1299 lung cancer cells, ectopic LOX-PP expression potently inhibited signaling by the endogenous mutant NRAS gene and the ability of these cells to form invasive colonies in Matrigel (46), while in prostate cancer cells, the addition of recombinant LOX-PP (rLOX-PP) protein decreased RAS signaling (45). Similarly, LOX-PP reduced fibronectin-stimulated signaling and the migration of Her-2/neu-driven breast cancer cells (49) and Ras signaling and the ability of pancreatic and breast cancer cells to form tumors in xenograft models in nude mice (30,31,46).…”
mentioning
confidence: 99%
“…LOX is synthesized as a 50-kDa inactive proenzyme (pro-LOX), which is N-and O-glycosylated within sites of the propeptide domain (45), secreted, and then cleaved to the functional C-terminal ϳ30-kDa enzyme and an ϳ18-kDa N-terminal lysyl oxidase propeptide (LOX-PP). Another major function of the LOX gene was discovered with the observation that its expression inhibited the transforming activity of the H-Ras oncogene in NIH 3T3 fibroblasts (6,22).…”
mentioning
confidence: 99%
“…1). During biosynthesis, the propeptide region is subject to N-linked (65) and O-linked glycosylation (68). Glycosylation of the propeptide has been shown to be essential for LOX enzymatic activity, but it is not required for secretion of the proenzyme (23).…”
Section: Lox Synthesis and Secretionmentioning
confidence: 99%
“…It has been shown that the LOX propep- tide achieves its tumor suppressor effects by reentering the cell following cleavage (24), although the precise mechanism by which this is achieved remains unknown. Indeed, the propeptide contains a putative nuclear localization sequence (68), which suggests that it may be actively directed to the nucleus once released from the proenzyme, and it has been shown to be capable of both repressing the oncogenic bcl-2 gene in breast cancer (71) and inhibiting FGF-2 signaling in prostate cancer (53). It has also been shown to possess an ability to inhibit signaling pathways that lead to the activation of nuclear factor-B (NF-B) in prostate and lung cancer (51,52,62), suggesting that there are likely multiple mechanisms by which it may exert tumor suppressor activity.…”
Section: Lox In Cancermentioning
confidence: 99%